Pengaturan Dampak Risiko Kecerdasan Artifisial dalam Tinjauan Perbandingan EU AI Act 2024 dan Hukum Positif di Indonesia - Ashyla Safani; Ahmad M. Ramli; Prita Amalia (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Currently, the digital era has penetrated most sectors of humanity, where one of the people who are penetrated is the Indonesian people. Data shows that internet users in Indonesia have reached 221 million, equivalent to 79.5 percent of Indonesia's total population. Indonesia is one of the countries with the largest number of internet users in the world. Some of them are the use of Artificial Intelligence in driving, in digital marketplace services, and in responding to consumer complaints. However, these things are not entirely free from the potential adverse risks that can befall consumers. So far, the Indonesian Positive Law regulation has not yet reached the regulation of the impact of potential adverse risks to consumers who use products containing Artificial Intelligence. On the other hand, the European Union has already regulated the impact of adverse risks in the use of Artificial Intelligence. Therefore, this research will try to adopt the norm from the European Union and initiate it as an answer to the regulation of the impact of risks in the utilization of Artificial Intelligence in the perspective of Indonesian Law.